PENGARUH VIDEO LEARNING PHBS: CARA MENCUCI TANGAN YANG BAIK DAN BENAR TERHADAP TINGKAT PEMAHAMAN ANAK USIA PRESCHOOL DALAM PENCEGAHAN PENYAKIT DIARE - Dina Carolina Hapsari; Tri Endah Pangastuti; Puspita, Shilfa (Jurnal Saintifik (Multi Science Journal), 2024)
Washing hands is sometimes considered unimportant for some people. Many people still say that washing hands is a waste of time, and people now prefer to use hand sanitizers rather than washing hands with running water and soap. According to WHO data (2014), washing hands with soap can reduce the risk of diarrhea by 40% and the risk of acute respiratory infections, including pneumonia, by 20%. Diarrhea is a complaint of loose or watery bowel movements that occur more than 3 times a day. Diarrhea is generally caused by consuming food or drinks contaminated with viruses, bacteria, or parasites. In this study, researchers wanted to determine the understanding of school-age children in PHBS: washing hands properly to prevent diarrhea by using the video learning method. Preschool children need learning that is easy to apply while playing, namely by using the video learning method where by using videos children can easily stimulate their sensors such as sight, hearing and the brain which stimulates motoric movements. The method used in this study is a quantitative method with a quasi-experimental pre-post test design using purposive sampling. The number of samples in this study was 40 respondents.